Naturally acquired antibodies to gametocyte antigens are associated with reduced transmission of Plasmodium vivax gametocytes to Anopheles arabiensis mosquitoes - Tebeje, Surafel K.; Chali, Wakweya; Hailemeskel, Elifaged; Ramjith, Jordache; Gashaw, Abrham; Ashine, Temesgen; Nebret, Desalegn; Esayas, Endashaw; Emiru, Tadele; Tsegaye, Tizita; Teelen, Karina; Lanke, Kjerstin; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Naturally acquired antibodies may reduce the transmission of Plasmodium gametocytes to mosquitoes. Here, we investigated associations between antibody prevalence and P. vivax infectivity to mosquitoes. A total of 368 microscopy confirmed P. vivax symptomatic patients were passively recruited from health centers in Ethiopia and supplemented with 56 observations from asymptomatic P. vivax parasite carriers. Direct membrane feeding assays (DMFA) were performed to assess mosquito infectivity; for selected feeds these experiments were also performed after replacing autologous plasma with malaria naïve control serum (n=61). The prevalence of antibodies against 6 sexual stage antigens (Pvs47, Pvs48/45, Pvs230, PvsHAP2, Pvs25 and PvCelTOS) and an array of asexual antigens was determined by ELISA and multiplexed bead-based assays. Gametocyte (ρ < 0.42; p = 0.0001) and parasite (ρ = 0.21; p = 0.0001) densities were positively associated with mosquito infection rates. Antibodies against Pvs47, Pvs230 and Pvs25 were associated with 23 and 34% reductions in mosquito infection rates (p<0.0001), respectively. Individuals who showed evidence of transmission blockade in serum-replacement DMFAs (n=8) were significantly more likely to have PvsHAP2 or Pvs47 antibodies. Further studies may demonstrate causality for the observed associations, improve our understanding of the natural transmission of P. vivax and support vaccine development.